Faktor-Faktor yang Memengaruhi Perkembangan Motorik Kasar pada Anak Usia Toddler (1-3 Tahun) di Wilayah Puskesmas Kota Pekalongan Tahun 2020 - Pedvin Ratna Meikawati; Ana Setyowati; Miftachul Jannah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Toddlers are children aged 12-36 months. Toddler is an important period in achieving intellectual development and growth. Development that controls body movements through coordinated activities between the central nervous system and muscles is called motor development. The aim of this research is to analyze the factors that influence gross motor development in toddler-aged children. Observational quantitative research method with a cross sectional approach, sampling using a simple random sampling technique with a total of 30 mothers who have toddler-aged children. The instrument used used an observation sheet and the analysis used used the Chi Square statistical test. The research results show that the majority of children with gross motor development are according to development, namely around 66.7% (20 people), while gross motor development is questionable, namely 26.6% (8 people) and gross motor development is deviant, namely 6.7% (2 people ). The research results show that the majority of children with gross motor development are according to development, namely around 66.7% (20 people), while gross motor development is questionable, namely 26.6% (8 people) and gross motor development is deviant, namely 6.7% (2 people ). The results of bivariate analysis show that there is a relationship between parental education (p value 0.001), simulation (p value 0.002), and socialization (p value 0.015) with children's gross motor skills. There is no relationship between the child's weight (p value 0.589), there is no relationship between exclusive breastfeeding (p value 0.653) and the child's gross motor development. It is hoped that parents who have toddler-aged children can increase their knowledge about gross motor development in children according to their age stages.